China's higher education expansion and its labor market consequences - Shi Li; Chunbing Xing (Institute for the Study of Labor (IZA), 2010)
Using a 1/5 random draw of the 1% census of 2005, we investigate how China's higher education expansion commenced in 1999 affects the education opportunities of various population groups and how this policy affects the labor market. Treating the expansion as an experiment and using a LATE framework, we find that higher education expansion increased the probability of go to college tremendously. Different populations 'benefit' from this policy differently however. Minority female, those from central-western region and from rural areas are less likely to benefit from it. One-child families are more responsive to this policy. Using higher education resources at the provincial level as another dimension of variation, and using a difference-in-difference strategy, we find that the education expansion decreased the within sector inequality of population with above high school (inclusive) education. This is primarily due to the increase of the income level for high school graduate. That of the college graduate deceased, but only slightly and not significantly.
Keywords: I2; J2; 330; China; higher education expansion; LATE; difference in difference; income level; Bildungspolitik; Bildungschancen; Hochschulpolitik; Wirkungsanalyse; Arbeitsmarkt; Einkommen; China